2017
DOI: 10.1007/s00262-017-2107-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1-induced high-grade hepatitis associated with corticosteroid-resistant T cells: a case report

Abstract: Effective treatment or prevention of immune side effects associated with checkpoint inhibitor therapy of cancer is an important goal in this new era of immunotherapy. Hepatitis due to immunotherapy with antibodies against PD-1 is uncommon and generally of low severity. We present an unusually severe case arising in a melanoma patient after more than 6 months uncomplicated treatment with anti-PD-1 in an adjuvant setting. The hepatitis rapidly developed resistance to high-dose steroids, requiring anti-thymocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 41 publications
0
49
0
1
Order By: Relevance
“…Although rare and generally of low severity, hepatitis due to immunotherapy with anti-PD1 has been reported. 23
10.1080/2162402X.2018.1484982-F0008Figure 8.SGT-53 prevents fatal xenogeneic hypersensitivity following repeated anti-PD1 administration in a syngeneic 4T1 breast cancer model. (A) Survival of BALB/c mice bearing 4T1 tumor after repeated dosing with anti-PD1 antibody alone or in combination with SGT-53.
…”
Section: Resultsmentioning
confidence: 99%
“…Although rare and generally of low severity, hepatitis due to immunotherapy with anti-PD1 has been reported. 23
10.1080/2162402X.2018.1484982-F0008Figure 8.SGT-53 prevents fatal xenogeneic hypersensitivity following repeated anti-PD1 administration in a syngeneic 4T1 breast cancer model. (A) Survival of BALB/c mice bearing 4T1 tumor after repeated dosing with anti-PD1 antibody alone or in combination with SGT-53.
…”
Section: Resultsmentioning
confidence: 99%
“…To most accurately compare protein expression levels between PBMC and TD we utilized a CD45‐based barcoding strategy, whereby a given patient's TD and PBMCs were first stained separately with CD45‐Pd104 and CD45‐Pd110, separately then washed and combined for subsequent antibody staining steps. Cells were stained for mass cytometry analyses as described . Briefly, cells were stained with 1.25 μ m Cell‐IDTM Cisplatin in PBS (Fluidigm) 3 min at room temperature and quenched by rapid addition of FCS.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were stained for mass cytometry analyses as described. 31 Briefly, cells were stained with 1.25 lM Cell-IDTM Cisplatin in PBS (Fluidigm) 3 min at room temperature and quenched by rapid addition of FCS. Cells were then washed twice in FACS buffer and then stained with a fluorophore-conjugated antibody cocktail for 20 min at 4°C.…”
Section: Cytof Profilingmentioning
confidence: 99%
“…Tacrolimus may be considered in case of failure after the administration of MMF. It has also been reported that antithymocyte globulin (ATG) can be used to treat severe hepatitis in patients who have failed to respond to corticosteroids . ICI‐related hepatotoxicity usually resolves within four to six weeks with the appropriate treatment.…”
Section: Immune‐related Hepatotoxicitymentioning
confidence: 99%